Friend or foe? Evidence that anxious people are better at distinguishing targets from non‐targets. (18th May 2017) - Ein‐Dor, Tsachi; Perry‐Paldi, Adi; Hirschberger, Gilad
Abstract: Armed conflict necessitates the ability to quickly distinguish friend from foe. Failure to make accurate shooting decisions may result in harm either to oneself or to innocent others. The factors that predict such rapid decision making, however, remain unclear. Based on social defense theory, we contend that people high on attachment anxiety possess characteristics that are particularly advantageous in this domain such that anxiously attached individuals will show greater vigilance and accuracy in a realistic shooting paradigm in which they must quickly distinguish between militants (people holding a gun) and innocents (people holding an item with the same color and shape as a gun—Coca‐Cola bottle, black wallet, and black mobile phone). Using signal detection theory algorithms, we calculated sensitivity in performing the behavioral shooting task [D(prime) ]. Results indicate that as expected, anxious people demonstrated significantly better shooting accuracy. Implication for contemporary violent conflict is discussed.